The impact of advanced metering infrastructure on residential electricity consumption: Evidence from California - Martin Heinrich Paschmann; Simon Paulus (Institute of Energy Economics at the University of Cologne (EWI), 2017)
One important pillar in the debate about energy-saving measures addresses energy conservation. In this paper, we focus on the deployment of advanced metering infrastructure to reduce the impact of limited information and bounded rationality of consumers. For California, we empirically analyze the influence of a statewide and policy-driven installation of advanced metering infrastructure. We apply synthetic control methods to derive a suitable control group. We then conduct a Difference-in-Differences estimation and find a significant negative impact of smart meters on monthly residential electricity consumption that ranges from 6.1 to 6.4%. Second, such an impact only occurs in non-heating periods and does not fade out over the analyzed time period.
Keywords: C91; D11; D12; D14; D83; 330; behavioral economics; bounded rationality; energy conservation; informational feedback; smart meters; residential electricity consumption